Polyphenols, Alkaloids, and Terpenoids Against Neurodegeneration: Evaluating the Neuroprotective Effects of Phytocompounds Through a Comprehensive Review of the Current Evidence - Enzo Pereira de Lima; Lucas Fornari Laurindo; Vitor Cavallari Strozze Catharin; Rosa Direito; Masaru Tanaka; Iris Jasmin Santos German; Caroline Barbalho Lamas; Elen Landgraf Guiguer; Adriano Cressoni Araújo; Adriana Maria Ragassi Fiorini; Sandra Maria Barbalho (Metabolites)
Neurodegenerative diseases comprise a group of chronic, usually age-related, disorders characterized by progressive neuronal loss, deformation of neuronal structure, or loss of neuronal function, leading to a substantially reduced quality of life. They remain a significant focus of scientific and clinical interest due to their increasing medical and social importance. Most neurodegenerative diseases present intracellular protein aggregation or their extracellular deposition (plaques), such as α-synuclein in Parkinson’s disease and amyloid beta (Aβ)/tau aggregates in Alzheimer’s. Conventional treatments for neurodegenerative conditions incur high costs and are related to the development of several adverse effects. In addition, many patients are irresponsive to them. For these reasons, there is a growing tendency to find new therapeutic approaches to help patients. This review intends to investigate some phytocompounds’ effects on neurodegenerative diseases. These conditions are generally related to increased oxidative stress and inflammation, so phytocompounds can help prevent or treat neurodegenerative diseases. To achieve our aim to provide a critical assessment of the current literature about phytochemicals targeting neurodegeneration, we reviewed reputable databases, including PubMed, EMBASE, and COCHRANE, seeking clinical trials that utilized phytochemicals against neurodegenerative conditions. A few clinical trials investigated the effects of phytocompounds in humans, and after screening, 13 clinical trials were ultimately included following PRISMA guidelines. These compounds include polyphenols (flavonoids such as luteolin and quercetin, phenolic acids such as rosmarinic acid, ferulic acid, and caffeic acid, and other polyphenols like resveratrol), alkaloids (such as berberine, huperzine A, and caffeine), and terpenoids (such as ginkgolides and limonene). The gathered evidence underscores that quercetin, caffeine, ginkgolides, and other phytochemicals are primarily anti-inflammatory, antioxidant, and neuroprotective, counteracting neuroinflammation, neuronal oxidation, and synaptic dysfunctions, which are crucial aspects of neurodegenerative disease intervention in various included conditions, such as Alzheimer’s and other dementias, depression, and neuropsychiatric disorders. In summary, they show that the use of these compounds is related to significant improvements in cognition, memory, disinhibition, irritability/lability, aberrant behavior, hallucinations, and mood disorders.